2020
DOI: 10.1002/jcsm.12603
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting as an independent predictor of survival in patients with chronic heart failure

Abstract: Background Skeletal muscle wasting is an extremely common feature in patients with heart failure, affecting approximately 20% of ambulatory patients with even higher values during acute decompensation. Its occurrence is associated with reduced exercise capacity, muscle strength, and quality of life. We sought to investigate if the presence of muscle wasting carries prognostic information. Methods Two hundred sixty-eight ambulatory patients with heart failure (age 67.1 ± 10.9 years, New York Heart Association c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 39 publications
2
69
0
Order By: Relevance
“…Our recent study reported that presence of osteoporosis assessed during hospital stay is an independent predictor of adverse events after discharge and fat mass index was closely associated with the extent of osteoporosis [ 53 ]. Result of a recent study showed that muscle wasting is an independent predictor of mortality in stable ambulatory HF patients [ 54 ]. Taken together with findings of the present study, muscle wasting may be an early marker for HF progression, whereas reduction in fat mass and bone mineral content may serve as a marker of cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study reported that presence of osteoporosis assessed during hospital stay is an independent predictor of adverse events after discharge and fat mass index was closely associated with the extent of osteoporosis [ 53 ]. Result of a recent study showed that muscle wasting is an independent predictor of mortality in stable ambulatory HF patients [ 54 ]. Taken together with findings of the present study, muscle wasting may be an early marker for HF progression, whereas reduction in fat mass and bone mineral content may serve as a marker of cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, cardiac dysfunction itself promotes skeletal muscle wasting, a complication known as cardiac cachexia. Furthermore, cardiac cachexia is an independent predictor of survival in chronic heart failure patients 5 in experimental models [6][7][8][9] and in up to 19.5% of heart failure patients, particularly those with reduced ejection fraction 10 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been known for decades that skeletal muscle structural and functional alterations are often associated with chronic heart failure (CHF) in noncachectic patients [ 123 ]. Muscle wasting not only strongly impairs CHF patients’ quality of life by impacting their daily activities through reduced physical capacity but has been also recently acknowledged as an aggravating comorbidity [ 124 ] and an independent predictor of survival [ 125 ]. These findings are driving a renewed attention from the scientific and clinical community, and technical advances and increased knowledge about muscle physiology have helped in opening new perspectives and identifying fat tissue as an important mediator in the cardiac–skeletal muscle crosstalk [ 126 , 127 ].…”
Section: Crosstalk Between Skeletal Muscle and Other Organs In Cacmentioning
confidence: 99%